A Case Study of Factors Contributing Successful Second Language Acquisition - Wardani, Maulidina Fahria; Anam, Syafi’ul; Mustofa, Ali (English Education : English Journal for Teaching and Learning, 2024)
This study investigates crucial elements for developing speaking fluency in English as second language, using a case study approach. It identifies internal and external factors influencing language acquisition, focusing on a 16-year-old vocational high school student in Indonesia. The research highlights the importance of linguistic input and a supportive environment. Factors such as early exposure to English through formal and informal education, family support, hobbies and a conducive home environment are shown to significantly impact language learning success. The study employs qualitative methods, including interview and speaking proficiency tests, to examine the subject’s learning process and identifies macroenvironmental and microenvironmental influences on her language development. It concludes that both types of environments are important for achieving proficiency in a second language.